4-3(2x+5)=5-(x-3)

Simple and best practice solution for 4-3(2x+5)=5-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3(2x+5)=5-(x-3) equation:


Simplifying
4 + -3(2x + 5) = 5 + -1(x + -3)

Reorder the terms:
4 + -3(5 + 2x) = 5 + -1(x + -3)
4 + (5 * -3 + 2x * -3) = 5 + -1(x + -3)
4 + (-15 + -6x) = 5 + -1(x + -3)

Combine like terms: 4 + -15 = -11
-11 + -6x = 5 + -1(x + -3)

Reorder the terms:
-11 + -6x = 5 + -1(-3 + x)
-11 + -6x = 5 + (-3 * -1 + x * -1)
-11 + -6x = 5 + (3 + -1x)

Combine like terms: 5 + 3 = 8
-11 + -6x = 8 + -1x

Solving
-11 + -6x = 8 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-11 + -6x + x = 8 + -1x + x

Combine like terms: -6x + x = -5x
-11 + -5x = 8 + -1x + x

Combine like terms: -1x + x = 0
-11 + -5x = 8 + 0
-11 + -5x = 8

Add '11' to each side of the equation.
-11 + 11 + -5x = 8 + 11

Combine like terms: -11 + 11 = 0
0 + -5x = 8 + 11
-5x = 8 + 11

Combine like terms: 8 + 11 = 19
-5x = 19

Divide each side by '-5'.
x = -3.8

Simplifying
x = -3.8

See similar equations:

| 12x+y=16 | | 2(x+21)=5x+21 | | 3(x+2)+2x=5x-2(x-4) | | 40-3x=17x | | 12p-6=8p-2 | | 4x+3x-4=3x+8 | | 7h+4=4h-5 | | 8x-2x+4=2x | | [10(3*x)+x]+[3x+10x]=88 | | 7d=-2d-18 | | 9x^2-225= | | 2x(2x-10)=-30+6x | | 2x-5(4-x)+3=14-(-5+2x) | | (2x^2+5x)(20x^2-7x-3)=0 | | 2y(y-1)=3-y | | 5(x+5)(x-10)=2(2.5x*x-1.9) | | 48=-8w | | 5(x+5)(x-10)=8.7 | | 9=2x-4 | | 5(x+5)(x-10)=12.5x-3.8 | | x-1.4=5.7 | | (x-7)(x+2)=x*x+10 | | x+2x-15=12 | | 5(-3-2x)=4 | | 4*8(x-4)=2x | | 2*8(x-4)=2x | | y=-0.02x^2+x+2 | | 2.1x-5.7=3.9(4.3-1.8x) | | 4x+2=3(x-1)+2 | | 4x-x=x+8 | | 4x+2=8x-14 | | 48-(18-58x)=28-(17+18x-57) |

Equations solver categories